New paleomagnetic constraints on central Asian kinematics: Displacement along the Altyn Tagh fault and rotation of the Qaidam Basin - Chen, Y.; Gilder, S.; Halim, N.; Cogne, J.P.; Courtillot, V. (My University, 2002)
In order to better understand the tectonic evolution of central Asia under the influence of the India-Asia collision, we carried out a paleomagnetic study of 1500 cores from 106 sites along the Altyn Tagh fault, in the Qaidam and Tarim basins, and on the Tibetan plateau. Samples were mainly collected from Jurassic to Neogene siltstones and sandstones. In most cases stepwise thermal demagnetization unblocks low and high temperature components carried by magnetite and hematite. Low temperature components are north and down directed and lie close to the recent geomagnetic field. High temperature components from 10 of 13 age/locality groups pass fold and/or reversal tests and likely represent primary remanent magnetizations. The ten overall mean directions display a complex pattern of vertical-axis block rotations that are compatible with a tectonic model of clockwise rotation of the Qaidam Basin and concomitant left-lateral slip on the Altyn Tagh fault. Two of the ten localities are rotated significantly counterclockwise; they lie adjacent to the Altyn Tagh fault zone, consistent with the idea that left-lateral strike-slip motion occurred along it. The age of counterclockwise rotation near the eastern extremity of the fault was dated as younger than 19 Ma. Three widely spread areas within the Qaidam Basin exhibit similar and significant clockwise rotations, on the order of 20 , with respect to the North China Block, Tarim and Eurasia. The mean of the three values is thought to represent the total rotation of Qaidam. Because the youngest rocks displaying clockwise rotations are Oligocene, the main phase of Qaidam Basin rotation, and hence shear on the Altyn Tagh fault, took place after or near the end of the Oligocene (~24 Ma). Upper Neogene strata located on the Qaidam Basin are not significantly rotated, thus tectonic deformation acting since the Upper Neogene (~5 Ma) is not resolvable by paleomagnetic methods. Given a 20° ±5° clockwise rotation of the Qaidam Basin with respect to the Tarim Basin, the maximum left-lateral displacement on the Altyn Tagh fault since 24 Ma is 500 ± 130 km.
Keywords: Altyn Tagh fault; paleomagnetism; central Asia; Qaidam; rotation; kinematics